Decentralized science (DeSci): definition, shared values, and guiding principles - Weidener, Lukas; Spreckelsen, Cord (Frontiers in Blockchain, 2024)
Rapid advancements in Distributed Ledger Technology (DLT), including blockchain, are foundational to a new era of digital innovation. This innovation has catalyzed the emergence of “Decentralized Science (DeSci),” a new concept and movement that aims to address the challenges of modern science. Given the novelty of the field of DeSci, this study aims to provide a comprehensive definition of the term and explore and conceptualize the shared values and guiding principles inherent to DeSci. To achieve these objectives, an exploratory literature review was conducted to identify and synthesize the scholarly and secondary literature. The search and selection process included six databases (PubMed, Google Scholar, Web of Science, IEEE Xplore, arXiv, and Social Science Research Network), focusing on the last 15 years (2008 to 2023). Owing to the novelty of DeSci, the literature review was supplemented by an anonymous online-based expert survey using a combination of single-choice and open-ended questions. The experts were selected based on predefined inclusion criteria related to their activities in the DeSci field. Seven studies were selected for evaluation from the scholarly literature, and additional 24 sources of information were included in the analysis. In the expert survey, 39 valid datasets were collected and analyzed. The synthesis of the exploratory literature review and expert survey results led to a comprehensive definition of “Decentralized Science” (DeSci) reflecting recurring themes. As no publications explicitly discussed or addressed the values or principles of DeSci in the literature review, a set of shared values and guiding principles was defined based on the expert survey results. This study proposes a comprehensive definition of DeSci and a set of shared values and guiding principles, highlighting the importance of future research in this area.